Motivation in education at a time of global change : theory, research, and implications for practice - Gonida, Eleftheria N.; Lemos, Marina S. (Advances in motivation and achievement ;, 2019)
This volume focuses on motivation in education underchanging and unsettling times and provides ideas on how global changes affectstudent and teacher motivation to learn and achieve.